On the Impact of Oil Prices on Sectoral Inflation: Evidence from World's Top Oil Exporters and Importers - Leila Ben Salem; Ridha Nouira; Christophe Rault (Institute of Labor Economics (IZA), 2024)
This paper investigates the impact of oil price variations on sectoral inflation for a sample of 10 top oil importing and exporting countries. Specifically, we analyze the effects of oil prices on the consumer price index using monthly data spanning the July 2009 to February 2021 period. Two nonlinear techniques are used to this end: The nonlinear autoregressive distributed lag approach (NARDL), and the Hansen's model (2000). Our econometric results first indicate that the effect of oil price on inflation tends to change across sectors and countries. Second, the inflationary effects of variations in oil prices are likely to affect the energy sector, such as transport and equipment, which are the most dependent on oil. Third, the effect of oil price exists for all countries, but it is stronger in oil-importing than in oil-exporting ones. Besides, the country most sensitive to the oil price level is China.
Keywords: C5; Q4; Q43; 330; oil-importing countries; panel threshold model; NARDL; sectoral inflation; oil price; oil-exporting countries